2022
DOI: 10.28991/cej-2022-08-12-05
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Environment and People’s Attitudes on Greywater Management in Slum Coastal Settlements

Abstract: The rapid population growth in many countries will ultimately impact the provision of essential services and engender many challenges, such as inadequate sanitation. Indonesia has an extensive coastline and densely populated coastal areas that have grown sporadically, creating slums. These areas have long been associated with poor greywater management. Greywater is dumped into beaches, roads, and yards without pre-treatment, thus harming the environment and society. This study aims to identify various factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…As per [76], coastal microplastics might stem from discarded waste, and it is noteworthy that Indonesia ranks second in oceanic plastic waste contributions globally [104]. Asmal et al [105,106] emphasized the challenges of plastic waste and broader waste management in the coastal regions bordering the Makassar Strait. Wicaksono et al [34] found microplastics in both water and sediment samples of the Tallo River, which flows into the Makassar Strait at Bosowa Beach.…”
Section: Microplastics Prevalence and Characterization Across Diverse...mentioning
confidence: 99%
“…As per [76], coastal microplastics might stem from discarded waste, and it is noteworthy that Indonesia ranks second in oceanic plastic waste contributions globally [104]. Asmal et al [105,106] emphasized the challenges of plastic waste and broader waste management in the coastal regions bordering the Makassar Strait. Wicaksono et al [34] found microplastics in both water and sediment samples of the Tallo River, which flows into the Makassar Strait at Bosowa Beach.…”
Section: Microplastics Prevalence and Characterization Across Diverse...mentioning
confidence: 99%
“…In addition to the negative impact of the natural factors on the coast, wastewater discharge from the pools into the water area of the lake by land users of the first line are located close to the coast. Rapid population growth in many countries will eventually affect the provision of basic utilities and may lead to problems regarding sanitary conditions on the shore [28]. Significant growth of holiday homes and resorts along the coast, without regard to local natural conditions, and the lack of a central wastewater collection system also put pressure on maintaining the natural ecological balance of the lakeshore.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia has already been referred to as a maritime country due to its 5.8 million km² of sea, of which 0.7 million km² are territorial waters and 2.3 million km² are made up of Sea Islands [3]. One of the benefits of having water resources is that, besides having natural resources, they can also support the aquatic ecosystem as well as being an important component of economic development [4][5][6]. However, researchers and scientists faced some limitations with respect to a lack of measurement data, including physical coastal water, water quality, and coastal zone management.…”
Section: Introductionmentioning
confidence: 99%